A preliminary study of identifying the visualization pattern of e-learning website for HEIS in Malaysia using card sorting method - Alberto Aning; Aslina Baharum (Scopus, 2020)
Complex and complicated graphical user interface contributes to slow inter-action and lack of emotional engagement between users and user interface design of e-learning websites in Higher Education Institution (HEI) in Malaysia. Considering the emergence of the Industrial Revolution 4.0 concept within HEI is inevitable, the e-learning platform will be an integral component towards the realization of Universities 4.0 visions in Malaysia. This study is the extension of the previous research on the web objects visualization pattern of e-learning identified. A preliminary study is conducted to determine web objects placement of visualization pattern based on the standard web objects for e-learning websites using card sorting methods. Three different focus group; students, academicians, and IT administrators will be participating in this study. This study aims to build a guideline for developers in designing emotional engaging for the user interface for e-learning web-sites in HEI. © 2020 Mattingley Publishing. All rights reserved.